Molecular dynamics study on the role of Ar ions in the sputter deposition of Al thin films - Gergs, Tobias; Mussenbrock, Thomas; Trieschmann, Jan (Journal of Applied Physics, 2022)
Compressive stresses in sputter deposited thin films are generally assumed to be caused by forward sputtered (peened) built-in particles and entrapped working gas atoms. While the former are assumed to be predominant, the effect of the latter on interaction dynamics and thin film properties is scarcely clarified (concurrent or causative). The overlay of the ion bombardment induced processes renders an isolation of their contribution impracticable. This issue is addressed by two molecular dynamics case studies considering the sputter deposition of Al thin films in Ar working gas. First, Ar atoms are fully retained. Second, they are artificially neglected, as implanted Ar atoms are assumed to outgas anyhow and not alter the ongoing dynamics significantly. Both case studies share common particle dose impinging Al(001) surfaces. Ion energies from 3 to 300 eV and Al=Arþ flux ratios from 0 to 1 are considered. The surface interactions are simulated by hybrid reactive molecular dynamics/force-biased Monte Carlo simulations and characterized in terms of mass density, Ar concentration, biaxial stress, shear stress, ring statistical connectivity profile, Ar gas porosity, Al vacancy density, and root-mean-squared roughness. Implanted Ar atoms are found to form subnanometer sized eventually outgassing clusters for ion energies exceeding 100 eV. They fundamentally govern a variety of surface processes (e.g., forward sputtering/peening) and surface properties (e.g., compressive stresses) in the considered operating regime.